Innovation in Architectural Education - Давыдова, Ольга Викторовна (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2018)
The choice of the form of representation of public experience due to the integration of fundamental science, the educational process itself and the needs of potential customers of project products is an actual problem for mastering cognitive, creative and organizational competences. The ability to predict their activities before the start of the project and the understanding that the activities of an architect do not begin and end with the project, but is a reflection of social ideals and values, and also aims at shaping the public consciousness of the future generation. Shifting the focus on self-awareness, self-assessment of its activities in the reflection of each stage is the basis for the formation of organizational competence necessary to fulfill social orders by the deadline. Organization of visibility in the relationship between teacher and students: 1) in understanding accepted and understood relevant information, 2) the possibility of self-unpacking of knowledge at the right time for students, within the framework of a holistic vision of the teacher’s world, 3) self-diagnosis before public evaluation of the designed product . Assertiveness of creative personality and life according to the rules, appropriate use in the creative process of typical and standard, the search for new architectural forms and unused opportunities based on the analysis of typical and exclusive similar projects in the actual problems to be solved. Self-prediction and self-esteem, self-realization before consciousness, social assessment in a changing world, ready for the manifestation of new (other) qualities.